Study of virtual cathodes formation during beam-wave interaction in the reltron oscillator - Mahto M.; Jain P.K. (My University, 2025)
In the present work, a high power microwave oscillator - reltron has been analyzed to investigate the virtual cathode formation mechanism during the beam-wave interaction. In reltron, a side coupled modulation cavity is used as its RF interaction structure containing three metal grids along the longitudinal direction. The space charge current responsible for the virtual cathode and its steady state electric field distribution has been analyzed. Space charge and beam impedance conditions for efficient device operation have been demonstrated. It has been shown that during the beam-wave interaction in the device, first a virtual cathode forms in the post-acceleration gap, and then the second virtual cathode develops between the first and second grids of the modulation cavity. These two virtual cathodes co-exist and cause the formation of a third virtual cathode between the second and third grids. At this instant, only the third virtual cathode remains, and for sustained device oscillation, this process repeats periodically in the device. The present study would be useful in understanding the beam-wave interaction mechanism as well as the design and development of efficient reltron devices. © 2017 Author(s).